Peningkatan Kemampuan Bahasa Inggris Siswa Kelas 5 Sekolah Dasar di Desa Manggari, Kecamatan Lebakwangi melalui Fun English Ramadhan - Turnip, Guido Tamba Raja; Mahdiyah, Fahra; Zulaikha, Farida; Rahma, Fitra Widya; Agustiana, Vina (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
English proficiency among elementary school students remains a challenge in many regions, including at Manggari village, Lebakwangi district. The “Fun English Ramadhan” program was designed to increase students' interest and motivation in learning English through a fun and interactive approach. This program incorporates various teaching methods such as Storytelling and Singing, Reading Theater, and Speech and Song Combination. The activities include socialization, training, technology integration, mentoring, evaluation, and sustainability planning. The results of the program indicate that this approach effectively enhances students’ confidence, verbal expression, and interest in learning English in a natural and enjoyable manner. By fostering an active and creative learning environment, this initiative is expected to serve as a best-practice model for English language instruction at the elementary school level.